Adult Cleft Lip Repair under Local Anesthesia: An Effective Technique in Resource-Poor Settings. (January 2013) - Eberlin, Kyle R.; Vyas, Raj M.; Abi-Haidar, Youmna; Sethna, Navil; Hamdan, Usama S.
Objective: In developing countries there are many adults with unrepaired cleft lip deformities. These countries often lack the equipment and personnel to provide general anesthesia for all patients; therefore, a technique for repair under local anesthesia would be useful. Method: A retrospective review was performed of 22 adolescent/adult patients on whom primary cleft lip repair was performed under local anesthesia in Bamako, Mali, in 2008 and 2009. Inclusion criteria for this technique were age greater than 12 with unilateral or bilateral deformity and ability to understand and tolerate the procedure under local anesthesia alone. Exclusion criteria included cardiopulmonary disease or inability to tolerate the procedure while awake. Demographic information and outcome data were collected including total time in the operating room, surgical time, and day of discharge. Results: Twenty-two primary cleft lip repairs were completed in 12 male and 10 female patients. Mean age was 22.3 years and mean weight was 50 kg. Overall, mean total operating room time was 145 minutes. Mean operating room time was significantly ( p < .01) longer in 2008 (159 minutes) than in 2009 (114 minutes). Although mean surgical time was 110 minutes, there was a similar significant (p = .03) decrease from 2008 (119 minutes) to 2009 (91 minutes). All patients tolerated the procedure without requiring intubation or intravenous sedation, and all were discharged the same day. Conclusion: Cleft lip repair in adults under local anesthesia is safe and effective. Improvements in technique and efficiency have made this valuable in developing countries.